Pushed or pulled: Adjustment and wellbeing among young children of forced and voluntary migrants - Robinson, J (My University, 2012)
Few studies of migrants collect longitudinal data, focus on early childhood, or compare children of forced or voluntary migrants. This study addresses some of those limitations by accessing data for children of forced and voluntary migrants in a large nationally representative database in a country of resettlement with a tradition of accepting both forced and voluntary migrants. The Longitudinal Study of Australian Children (LSAC) traces the development of two cohorts, infants and preschool-age children, every two years. This paper focuses on data collected from both cohorts when the children were aged 4 to 6 years. It compares the developmental context, preschool/school adjustment, school readiness and emotional and behavioral problems of young children whose parents were born in three general locations: Non-English speaking countries that almost exclusively contribute forced migrants to Australia (e.g., Sudan, Afghanistan); Non-English speaking countries that almost exclusively contribute voluntary migrants to Australia (e.g., India, China); and Australia. Information about children’s developmental context and their social and emotional problems were obtained from parents and preschool/school teachers using the Strengths and Difficulties Questionnaire. Teachers also reported on preschool/school adjustment using the Student-Teacher Relationship Scale. Children of forced migrants were more likely than children in other groups to experience disadvantage in several dimensions of their developmental context. Outcome variables differed in the extent to which parents’ migration status explained independent variance in outcomes. Parent- and teacher-reports showed that both groups of children were resilience on some dimensions of development.
Keywords: Education and Training -- School readiness; Child Development; Disadvantage; Children -- Outcomes; Culture -- Immigrants; Childhood and child development; Learning, education and training; Migration and settlement; Children; Child Development; Education and Training; Culture; Disadvantage; Immigrants; Outcomes; School readiness; Childhood and child development; Learning, education and training; Migration and settlement